Probability of pregnancy to artificial insemination either after detected oestrus or at a fixed time in dairy cows: Influence of intrinsic and extrinsic factors in a large-scale, on-farm study - Ungerfeld, Rodolfo; Kmaid, Sergio; Baldi, Fernando [UNESP]; Salveraglio, Virginia (Wiley, 2021)
The first aim of this study was to determine the influence of the procedures [hormonal treatments for fixed time artificial insemination (FTAI) versus insemination at spontaneous oestrus (SEAI)] on several sequential inseminations (AI). A second aim was to determine the influence of some intrinsic and extrinsic factors and their interactions, including characteristics of the animals such as age, season, farm, sire, and AI technician on the response to both procedures. A retrospective analysis was performed from a data base of 120.807 AIs of healthy cows with at least 40–70 days post-partum at first service. Overall, FTAI achieved slighter greater pregnancy rates than insemination after detected oestrus. The second AI seems to be a key insemination as effects of sire and technician were greater than in the following ones. The use of FTAI or SEAI in one AI did not affect the results of the following AIs, regardless if FTAI or SEAI procedures were used in that AI. Technician had greater variation than sire or farm on final pregnancy rate. The results of each sire for pregnancy rate varied according to the type of insemination, with sires achieving greater results with one or other procedure. Pregnancy rate was positively related to the days in milk in the first two AIs. Results were greater in autumn than in spring services.
Keywords: fertility; Holstein; inseminator; ovulation; sire; synchronization